The prevalence of undernutrition and associated factors among preschool children: Evidence from Pakistan Demographic and Health Survey 2017–18. (December 2020) - Naz, Lubna; Kumar Patel, Kamalesh; Evan Uzoma, Ifeoma
Highlights: South Asia had the highest (35 percent) stunted growth of under-fives in the world in 2017. The prevalence of wasting was the highest among children age 6–11 months in Pakistan. The prevalence rates of stunting and underweight were lower among preschoolers whose mothers had higher secondary education. The rural household had 33 percent lower wasting among under-fives compared to urban. Abstract: The malnutrition adversely affects the survival, health, and cognitive abilities of the preschoolers. This article examines the prevalence of undernutrition and the proximate factors of stunting, wasting, and underweight in Pakistan. The study used a sample of 3, 575 under-five children extracted from the Pakistan Demographic and Health survey 2017–18. The nutritional status was assessed by using z-scores of height for age (HAZ), weight for height (WHZ), and weight for age (WAZ). The data was prior adjusted for the survey design and reference values (<-2 for HAZ, WHZ, and WAZ) of stunting, wasting, and underweight. The study used both bivariate and multivariate methods. Results showed that more than one third (38 percent) of under-fives are stunted, 8 percent wasted, and 23 percent underweight in Pakistan. The binary regression results reveal that children whose mothers maintained birth-interval of more than three years were associated with 34 percent and 28 percent lower odds to become stunted and underweight, respectively, compared to those whose mothers opted for shorter birth intervals. Children born to mothers with higher secondary education and in the older age group have lower odds of stunting and wasting than children whose mothers were uneducated and younger. Wealthier households have lower odds of the prevalence of stunting and wasting than poorer. The research findings may be used to integrate national nutritional strategies with girls' education and maternal healthcare plans and devise social protection programs for resource-poor families with a higher prevalence of undernutrition among under-five children.